2022
DOI: 10.4103/jpbs.jpbs_155_22
|View full text |Cite
|
Sign up to set email alerts
|

Propofol's Efficacy and Outcomes on Anxious Children's Behavior in the Course of Dental Therapy

Abstract: Introduction: Tranquility therapies have recently been more popular as a means of reducing anxiety amongst children in the course of painful diagnostic and therapeutic procedures. As a result, a variety of techniques (oral tranquility, intravenous (IV) tranquility) have been developed to assist practitioners in order to deal with such instances. The goal of this trial was to see how effective propofol could be in calming anxious youngsters during the course of dental therapy. The interventional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, the GA can’t fundamentally solve CDF and even aggravate CDF symptoms in children, resulting in worse oral health status in children intervened by GA [ 35 ]. Protective fixation, as a traditional intervention in stomatology, has been widely applied in oral diagnosis and treatment of preschool children, and some studies have revealed that the use of protective fixation measures can improve children’s treatment compliance [ 36 ]. The results indicated that protective fixation measures could not alleviate anxiety in children with CDF.…”
Section: Discussionmentioning
confidence: 99%
“…However, the GA can’t fundamentally solve CDF and even aggravate CDF symptoms in children, resulting in worse oral health status in children intervened by GA [ 35 ]. Protective fixation, as a traditional intervention in stomatology, has been widely applied in oral diagnosis and treatment of preschool children, and some studies have revealed that the use of protective fixation measures can improve children’s treatment compliance [ 36 ]. The results indicated that protective fixation measures could not alleviate anxiety in children with CDF.…”
Section: Discussionmentioning
confidence: 99%